2018
DOI: 10.3389/fendo.2018.00290
|View full text |Cite
|
Sign up to set email alerts
|

Central Effects of 3-Iodothyronamine Reveal a Novel Role for Mitochondrial Monoamine Oxidases

Abstract: 3-Iodothyronamine (T1AM) is the last iodinated thyronamine generated from thyroid hormone alternative metabolism found circulating in rodents and in humans. So far, the physiopathological meaning of T1AM tissue levels is unknown. Much is instead known on T1AM pharmacological effects in rodents. Such evidence indicates that T1AM acutely modifies, with high potency and effectiveness, rodents’ metabolism and behavior, often showing inverted U-shaped dose–response curves. Although several possible targets for T1AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…T1AM, pharmacologically delivered to rodents, presents a short half-life being rapidly degraded to TA1 (Manni et al, 2012) by monoamine oxidases (MAO) or by deiodinases (Laurino et al, 2015). Typically, T1AM pharmacological effects onset within 15 min from amine administration describing inverted dose-effect curves which are modulated by monoamine oxidase inhibitors, thus suggesting that the production of TA1 may be part of T1AM effects (Laurino et al, 2018b) including memory stimulation and hyperalgesia (Manni et al, 2013). Recently, Bellusci et al (2017) confirmed the participation of TA1 in the T1AM-induced activation of neuroprotective pathways including autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1AM, pharmacologically delivered to rodents, presents a short half-life being rapidly degraded to TA1 (Manni et al, 2012) by monoamine oxidases (MAO) or by deiodinases (Laurino et al, 2015). Typically, T1AM pharmacological effects onset within 15 min from amine administration describing inverted dose-effect curves which are modulated by monoamine oxidase inhibitors, thus suggesting that the production of TA1 may be part of T1AM effects (Laurino et al, 2018b) including memory stimulation and hyperalgesia (Manni et al, 2013). Recently, Bellusci et al (2017) confirmed the participation of TA1 in the T1AM-induced activation of neuroprotective pathways including autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, irrespective of which is the plasma membrane receptor recognized, T1AM may also generate, inside cells TA1, a metabolite endowed of an its own signaling capacity and pharmacological activities. Which one of these mechanisms (the plasma membrane and the intracellular ones) prevails could depend on the expression levels of plasma membrane targets and on the amine oxidase cell kit (Laurino et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Brain histamine (neuronal and not neuronal) is part of the mediators involved in the control of hypothalamic governed behaviors and it is also endowed of neuroprotective effects against excitotoxic damage (Kukko-Lukjanov et al, 2006). Furthermore, brain histamine is also part of the mechanisms of the neuroprotection offered by T3 metabolites (Cao et al, 2009; Laurino et al, 2018a,b). On the other hand, it is well assessed that histamine also controls the release of TSH (Roberts and Calcutt, 1983), a finding potentially linking the histaminergic system to the control of thyroid function.…”
Section: Histamine and The Thyroidmentioning
confidence: 99%
“…Histamine levels were found high during the embryonic brain development (Pearce and Schanberg, 1969) and Sabria et al (1987) reported T3 as possible candidate for controlling brain mast cells number and, consequently, the levels of brain histamine during development. Till now there is no evidence that brain mast cells may contain T3 but there are evidence that T3 metabolites activate the histaminergic system in the brain as well as in periphery (Laurino et al, 2018a,b).…”
Section: Histamine and The Thyroidmentioning
confidence: 99%
See 1 more Smart Citation